European Charter on Regional and Minority Languages and Georgia - Dadiani, Eka; Gvazava, Merab; Sherozia, Revaz (Actual Problems of Kartvelology, 2013)
European Charter of Regional and Minority Languages is a significant international document the aim of which is the protection of ‘European historical regional or minority languages; it encourages the protection and development of the European cultural treasure and traditions’. Charter does not refer to veriaties (dialects) of the state language and the language of the migrants. Therefore, it does not refer neither to the so called ‘Kartvelian languages’ (Megrelian-Laz and Svan), nor to Armenian, Azeri, Russian, Greek, Ukrainian and other languages. There is no historical, autochthonous ethnic minority in Georgia, especially the endangered one. If we strictly follow the principles of the ‘Language Charter’, Georgia can ratify the ‘Charter’ without listing regional and minority languages. We regard that the ratification of the ‘Language Charter’ will be possible once the Georgian ethnic-linguistic situation is analyzed and the status of languages in the country is appropriately defined.